PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN PENANAMAN POHON DALAM MENJAGA LINGKUNGAN HUTAN MANGROVE TANJUNG PASIR - ANGGRENI, PUTRI (UNHI Press, 2025)
Reforestation in mangrove forests is one of the important activities that must be implemented conceptually in dealing with environmental crises and preserving nature. The coastal area of Tangerang Regency, precisely in Muara Village, Teluk Naga Subdistrict, is covered with mangrove trees. The location of the mangrove forest is close to the construction site of PIK 2, which is also close to the North Coast of Jakarta. Compared to other beach tours around Tangerang, this mangrove forest tour is still relatively quiet. Padal mangrove tourist attraction is an educational place to get to know the aquatic ecosystem and to learn more about the benefits of mangroves for the coast and the creatures that live in it. This Community Service Programme (PKM) aims to provide knowledge about the importance of greening and preserving nature to the community. The implementation of this PKM uses a method that consists of several stages of implementation, namely the preparation stage, implementation in the form of preparation processes, activities, and evaluation.